Conversations among Competitors - Stein, Jeremy C (American Economic Review, 2008)
I develop a model of bilateral conversations in which players honestly exchange ideas with their competitors. The key to incentive compatibility is complementarity in the information structure: a player can generate a new insight only if he has access to his counterpart's previous thoughts on a topic. I then examine a social network in which A has a conversation with B, then B has a conversation with C, and so on. Relatively underdeveloped ideas can travel long distances over the network. More valuable ideas, by contrast, tend to remain localized among small groups of agents. (JEL D83)